Identity and difference: Essays on music, language and time - Dejans, Peter; Cross, Jonathan 1961-; Harvey, Jonathan 1939-2012; Lachenmann, Helmut 1935-; Wellmer, Albrecht; Klein, Richard (Leuven Leuven University Press, 2004)
This volume is a collection of essays based on lectures given at the Orpheus Institute in Ghent at various occasions between 2000 and 2004.Two of our five distinguished authors are British, three are Germans. Two are prominent composers and both keen and provocative writers about music; one is a musicologist and daring critic who specializes in contemporary music. There are also two philosophers and Adorno specialists that deal with such fundamental and highly complex matters as music and language, and music and time.All authors subscribe to the same seriousness of purpose, so that you may find reminiscences of one text in the others, which will make for a fascinating read. Moreover, this book is all about the current state of music, about thinking, speaking, and writing about music in the immediate aftermath of that stirring and fascinating twentieth century.